WAYS TO ESTABLISH THE PHYSICAL FITNESS OF QUALIFIED HANDBALL PLAYERS BY PROFESSIONALS - Bazarbayev Paraxat Amangeldiyevich (Western European Studies, 2025)
This article will explore ways to develop the physical fitness of qualified handball players with the help of special exercises. The game of handball involves the development of physical and functional qualities that require a high level of training of athletes. The study analyzes the importance and effectiveness of specific training methodologies to increase the speed, strength, endurance, agility and reaction rate of athletes. The article presents modern approaches such as plyometric exercises, high intensity interval training (HIIT), strength and agility enhancing exercises. These techniques are important for improving the overall fitness of athletes, protecting against injury, and showing maximum results during competitions. The results of the study indicate the need to apply new techniques in improving the preparatory processes of qualified handball players.
Keywords: Handball players; physical training; special exercises